Penggunaan Energi Di Atas Kebutuhan Hidup Pokok Pada Ayam Broiler Selama Umur 2 - 6 Minggu Di Daerah Tropis - Ahadiyah Yuniza (Universitas Andalas, 2006)
An experiment was conducted to study the effect of excess energy intake above the level of energy requirement for maintenance (ERM) on the abdominal fat deposition. Five diets were formulated with different energy levels of above ERM i.e.: (A) ERM, (B) ERM + 30 kcal, (C) ERM + 60 kcal, (D) ERM + 90 kcal, and (E) ERM + 120 kcal. The diets were then offered for 4 weeks to 32 broiler chickens of two weeks old. Parameters measured included: body weight gain, abdominal fat, body fat and protein content. Results indicated that restriction of energy intake could not significantly reduce the abdominal fat deposition of broiler. During the growing period, the excess energy intake was not used for muscle growth maximally, but also used to deposit abdominal fat.